Development of the classical Islamic guarantee through fatwa in modern Islamic banking - Ab Rahman, Suhaimi (Faculty of Economics and Business, Universiti Malaysia Sarawak, 2018)
It was circa 749-1850 of the Islamic era that sophisticated rules and principles including the guarantees were developed. This paper is to clarify the application of the classical Islamic law of guarantee, kafalah, in modern banking. Important legal texts that include the Qur’an, the Sunnah of the prophet Muhammad SAW and the classical manuals of Islamic law have been examined to understand the nature of classical Islamic law of guarantee. A number of fatwas or resolutions of the guarantee were also examined to understand the meaning and the extent the classical law is applicable in modern banking. The results show that the basis of modern guarantee was made upon the rules and principles of al-kafalah that have been developed circa 1200 years ago. However, the principles of classical Islamic law of guarantee have been expanded and developed to allow for the charging of fees despite the contract is gratuitous in nature. The paper concludes that Islamic law, fiqh, is progressive in nature as it is a situational inference to Allah’s will; and it is upon interpretation and deduction that the rules in Islamic Shari’ah could be appreciated and developed to suit modern circumstances.